A multi criterion approach for the selection of optimal bench width in open pit mines - Hadjigeorgiou, John; Grenon, Martin; Kabuya Mukendi, Joseph (2020)
Open pit design has to address the stability of benches, inter ramp and the global stability of the pit walls. Benches are required to provide a safe working environment for personnel and equipment. Limit equilibrium techniques based on available geomechanical data are used to design safe face slope angles and bench heights. A further consideration is the choice of an appropriate catch basin and bench width. It is expected that a bench should be wide enough to contain any instability from the benches above. This paper addresses the selection of minimum bench width based on legislation, company policy, operating practice and a series of technical criteria. A case study from a mining project in the Canadian arctic is employed to illustrate that the choice of any design criterion can lead to different recommendations. This paper presents systematic multi-criterion based approach that can lead to a more reliable and informed design of optimal bench width in open pit mines.